Platform independent web-based telecardiology for connected heart care - Kam, Kui Lin (Penerbit UTM Press, 2016)
Most of the commercial telecardiology systems are platform-dependent and operating system (OS)-dependent. This causes inconvenience to medical officer for retrieving data from database and hence reduce the work efficiency. In this paper, a platformindependent and OS-independent web-based telecardiology system, named VirtualDave System, is proposed based on client-server model and developed in Hypertext Markup Language 5 (HTML5), Active Server Pages (ASP) scripting and C# languages. This system allows users to log on and access the patient medical data from any technology devices that equipped with web browser and internet access. Besides, it also allows targeted users to communicate and get remote medical consultation without long distance traveling and long-time queuing. Verification result shows that this proposed system could be executed in any platform regardless the OS. This web-based telecardiology could significantly help to improve the health care services especially in rural area.